2019
DOI: 10.1088/2515-7655/ab2f1e
|View full text |Cite
|
Sign up to set email alerts
|

Energy harvesting using thermoelectricity for IoT (Internet of Things) and E-skin sensors

Abstract: With the increasing demand for Internet of Things (IoT) with integrated wireless sensor networks (WSNs), sustainable power supply and management have become important issues to be addressed. Thermal energy in forms of waste heat or metabolic heat is a promising source for reliably supplying power to electronic devices; for instance, thermoelectric power generators are widely being researched as they are able to convert thermal energy into electricity. This paper specifically looks over the application of therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 90 publications
(135 reference statements)
0
21
0
Order By: Relevance
“…Thermal energy in forms of waste heat or metabolic heat is a promising and dependable power source for electronic devices; for example, TEGs are widely being investigated for their ability to convert thermal energy into electricity through Seebeck effect. These materials, therefore, have enormous potential for meeting a part of our energy needs and in enabling self-powered sensors, but improved materials and optimized device geometries are required before this can be realized [9,10]. The thermoelectric (TE) performance of a material can be considered by the parameter, figure-of-merit (ZT), defined as 2…”
Section: Introductionmentioning
confidence: 99%
“…Thermal energy in forms of waste heat or metabolic heat is a promising and dependable power source for electronic devices; for example, TEGs are widely being investigated for their ability to convert thermal energy into electricity through Seebeck effect. These materials, therefore, have enormous potential for meeting a part of our energy needs and in enabling self-powered sensors, but improved materials and optimized device geometries are required before this can be realized [9,10]. The thermoelectric (TE) performance of a material can be considered by the parameter, figure-of-merit (ZT), defined as 2…”
Section: Introductionmentioning
confidence: 99%
“…The IoT with integrated wireless sensor networks become important issues that increasing demand for renewable power supply and management. H. Park et al [99] have demonstrated the application of TEG energy harvesting system as a renewable energy source for IoT, including wireless sensor networks. They investigated the models of the human thermoregulatory process on body heat harvesting.…”
Section: Figure 2 the Processes Of An Electrical Energy Recovery System Of Tegsmentioning
confidence: 99%
“…6,7 Harvesting energy from human body via TEGs thus represents a promising direction in designing self-powered wearable electronics, especially when the cutting-edge technologies have significantly reduced their power requirement, suggesting a bright future for the practical applications of thermoelectric energy harvesting. [8][9][10] Whereas, existing TEGs are primarily fabricated using rigid or non-stretchable components, which restrains their capability to conform to human skin or accommodate human motions. [11][12][13][14][15] To meet the requirement of wearability, TEGs must possess high mechanical flexibility and preferable stretchability, and in the meantime can provide consistent energy output even having encountered mechanical damages.…”
Section: Introductionmentioning
confidence: 99%